Community Empowerment in Facing Covid-19 Disaster by KKN Students Of Universitas Sebelas Maret in Wonosobo District - Chatarina Muryani; Fransisca Trisnani Ardikha Putri; Puji Lestari; Rahendhiki Ratik Galindra; Ainaya Nurrachma Hakim; Almara Yoyok Arighynata; Danang Mika Daya; Dika Ulfatus Sa'adah; Rima Reniesa Pelita Rianti; Dwitama Alphin Usdianto; Lulu Febriana Damayanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Sebelas Maret University Real Work Lecture (KKN) during the COVID-19 pandemic was still carried out with a focus on problems that occurred during the COVID-19 pandemic. The location for the Covid-19 KKN placement is also specifically in the Neighborhood (RT) where the KKN students live. In the Wonosobo Regency area there are 10 Sebelas Maret University students who are undergoing KKN, they are members of the Group 170 UNS Covid-19 Batch-2 KKN.These students have successfully carried out community empowerment activities in the form of (1) Socialization to the community about COVID-19 and food security, (2) Training and practices related to family resilience in the face of the COVID-19 pandemic, including training and practice of making masks, making hand sanitizers, planting vegetables in hydroponics and planting in pots and family waste. Based on the family resilience survey that has been carried out, as many as 70% of the respondent's families are in the high family toughness category.